On the need to study the laws of «formulaic grammar» in Kazakh epic text zhyrau XV-XVIII centuries (Herald of Journalism, 2020)
The article says that poetry zhyrau of different heroic and romantic pathos, the spirit of the liberation struggle, the wealth of artistic forms, and that our time in the tradition of akyns dominated by traditional, sustain- able stylistic formula and oral-stylistic technique that shed because of its ancient syncretic musical-verbal natural light on the genesis and evolution of the various art forms of modern art, including poetic, of course, goes back to the epic, myth and ritual.
Keywords: «Formulary grammar», the epic genre, oral individual cre- ativity, zhyr, zhyrau, genesis, ritual, ceremony.